Calidad de la ética en el proceso de afiliación y verificación de los promotores del programa pensión 65 de la unidad territorial Loreto 2023 - Pezo Rios, Alfredo (2025)
The purpose of this research was to determine how ethical quality is related to the process of affiliation and verification of the promoters of the Pension 65 programme of the territorial unit in Loreto, 2023. Opting for a basic study, correlational level and non-experimental cross-sectional design, the sample consisted of 80 promoters for the survey conducted with a questionnaire for data collection. The findings show that the quality of ethics is perceived as "good" ('65%); the process of affiliation and verification is also rated as "good" (65%); therefore, it is determined that between the variables there is a significance of p=0.000. Likewise, the dimensions autonomy, responsibility and professional competence have a significance of p=0.000, these dimensions are significantly and positively related to the process of affiliation and verification.